Nonlinear Analysis of Visual Evoked Potentials Elicited by Color Stimulation - Momose, K.; Komiya, K.; Uchiyama, A. (Methods of Information in Medicine, 1997)
The relationship between chromatically modulated stimuli and visual evoked potentials (VEPs) was considered. VEPs of normal subjects elicited by chromatically modulated stimuli were measured under several color adaptations, and their binary kernels were estimated. Up to the second-order, binary kernels obtained from VEPs were so characteristic that the VEP-chromatic modulation system showed second-order nonlinearity. First-order binary kernels depended on the color of the stimulus and adaptation, whereas second-order kernels showed almost no difference. This result indicates that the waveforms of first-order binary kernels reflect perceived color (hue). This supports the suggestion that kernels of VEPs include color responses, and could be used as a probe with which to examine the color visual system.
Keywords: VEP; Color Response; Color Adaptation; Binary Kernel